Republic of Fiji : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2019)
This Article IV Consultation highlights that the economy is recovering well from several natural disasters, supported by accommodative fiscal and monetary policies. Growth performance picked up in recent years with improved political stability, though average growth rates were still lower than in other emerging and developing countries. Fiscal buffers have been used and external conditions, including oil prices and growth prospects of main trading partners, are becoming less favorable. Improving the overall business environment and governance is expected to raise potential growth by mobilizing private investment, enhancing productivity, and diversifying the economy. An improvement in the overall business environment is essential to achieve the ambitious growth targets laid out in the National Development Plan. Streamlining procedures to do business, accelerating the activation of the credit reporting agency, and reducing tax compliance costs has been recommended.